Fibroblast growth factor 7 releasing particles enhance islet engraftment and improve metabolic control following islet transplantation in mice with diabetes. Issue 9 (2nd February 2021) - Alwahsh, Salamah M.; Qutachi, Omar; Starkey Lewis, Philip J.; Bond, Andrew; Noble, June; Burgoyne, Paul; Morton, Nik; Carter, Rod; Mann, Janet; Ferreira‐Gonzalez, Sofia; Alvarez‐Paino, Marta; Forbes, Stuart J.; et al.
Abstract : Transplantation of islets in type 1 diabetes (T1D) is limited by poor islet engraftment into the liver, with two to three donor pancreases required per recipient. We aimed to condition the liver to enhance islet engraftment to improve long‐term graft function. Diabetic mice received a non‐curative islet transplant ( n  = 400 islets) via the hepatic portal vein (HPV) with fibroblast growth factor 7‐loaded galactosylated poly(DL‐lactide‐co‐glycolic acid) (FGF7‐GAL‐PLGA) particles; 26‐µm diameter particles specifically targeted the liver, promoting hepatocyte proliferation in short‐term experiments: in mice receiving 0.1‐mg FGF7‐GAL‐PLGA particles (60‐ng FGF7) vs vehicle, cell proliferation was induced specifically in the liver with greater efficacy and specificity than subcutaneous FGF7 (1.25 mg/kg ×2 doses; ~75‐µg FGF7). Numbers of engrafted islets and vascularization were greater in liver sections of mice receiving islets and FGF7‐GAL‐PLGA particles vs mice receiving islets alone, 72 h posttransplant. More mice (six of eight) that received islets and FGF7‐GAL‐PLGA particles normalized blood glucose concentrations by 30‐days posttransplant, versus zero of eight mice receiving islets alone with no evidence of increased proliferation of cells within the liver at this stage and normal liver function tests. This work shows that liver‐targeted FGF7‐GAL‐PLGA particles achieve selective FGF7 delivery to the liver‐promoting islet engraftment to help normalize blood glucose levels with a good safety profile. Abstract : Cotransplantation of islets with liver‐targeted, biodegradable microparticles loaded with fibroblast growth factor 7 into livers of diabetic mice leads to short‐term hepatocyte proliferation and improves islet engraftment with superior long term glycemic control versus transplantation with islets alone. See the editorial on page 2927 .